Effects on Number of Supports on Vibration and Stress Distribution for Piping System - Abdul Basith, Mohammad Sobir (IRC, 2020)
Fluid induced vibration are commonly faced by industry that are related with piping and pipeline. This phenomenon needs to take on seriously as it can leads to loss and danger to the plant. Additional of pipe support could reduce the vibrational behaviour of the system. However, the additional of pipe supports may lead to the increase in stress acting on the piping and consequently causes crack and leaking issue. This study investigates the effects of number of supports on pipe stress and vibrational behaviour of the piping system. Modal analysis was conducted to investigate the natural frequency and mode shape of the overall piping system, while static structural analysis was conducted in ANSYS to determine the pipe stress. In this study, vibration issue was managed to be improve by 81.62%. It is considered solved as the value of natural frequency is more than 15Hz which been recommended by ASME 2016. However, their stress value at critical points still exceeded the allowable stress limit by 74%. This shows that the optimizing of natural frequency and pipe stress of the piping could not be achieved through the addition of supports alone.